2018
DOI: 10.15252/embj.201899238
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial inner membrane permeabilisation enables mt DNA release during apoptosis

Abstract: During apoptosis, pro‐apoptotic BAX and BAK are activated, causing mitochondrial outer membrane permeabilisation (MOMP), caspase activation and cell death. However, even in the absence of caspase activity, cells usually die following MOMP. Such caspase‐independent cell death is accompanied by inflammation that requires mitochondrial DNA (mtDNA) activation of cGAS‐STING signalling. Because the mitochondrial inner membrane is thought to remain intact during apoptosis, we sought to address how matrix mtDNA could … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
335
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 384 publications
(347 citation statements)
references
References 45 publications
11
335
0
1
Order By: Relevance
“…Indeed, they found that treatment of cells with BCL‐2 targeting drugs, called BH3 mimetics, was able to stimulate the release of the pro‐inflammatory cytokines IL‐6, IL‐8, CXCL1 and FGF‐2 in the absence of cell death. Consistent with recent findings, this pro‐inflammatory phenotype was dependent on BAX/BAK and STING (McArthur et al , ; Riley et al , ). Accordingly, they found that depleting cells of mtDNA, using a mitochondrial‐targeted viral DNase, was able to reduce IL‐6 secretion following BH3‐mimetic treatment.…”
Section: Limited Mitochondrial Permeabilisation Drives Inflammation Isupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, they found that treatment of cells with BCL‐2 targeting drugs, called BH3 mimetics, was able to stimulate the release of the pro‐inflammatory cytokines IL‐6, IL‐8, CXCL1 and FGF‐2 in the absence of cell death. Consistent with recent findings, this pro‐inflammatory phenotype was dependent on BAX/BAK and STING (McArthur et al , ; Riley et al , ). Accordingly, they found that depleting cells of mtDNA, using a mitochondrial‐targeted viral DNase, was able to reduce IL‐6 secretion following BH3‐mimetic treatment.…”
Section: Limited Mitochondrial Permeabilisation Drives Inflammation Isupporting
confidence: 91%
“…Mitochondrial permeabilisation elicits inflammation in multiple ways. For instance, recent work shows that mtDNA is ejected from permeabilised mitochondria during cell death, activating cGAS‐STING‐dependent type I interferon production (McArthur et al , ; Riley et al , ). While dispensable for cell death, apoptotic caspases serve to dampen inflammation by targeting multiple cellular processes (McIlwain et al , ; Ning et al , ).…”
Section: Limited Mitochondrial Permeabilisation Drives Inflammation Imentioning
confidence: 99%
“…In addition, although Riley et al () could not follow mtDNA release in caspase proficient conditions due to fast cell demise, McArthur et al () demonstrated that this process also takes place under caspase activation. These observations underline a faster kinetics of apoptotic cellular dismantling compared to MIMP and thus suggest that the pro‐inflammatory role of MOMP is only relevant under caspase‐deficient conditions.…”
Section: Kinetics Of Momp‐driven Inflammationmentioning
confidence: 99%
“…How mtDNA reaches the cytosol from the mitochondrial matrix to activate cGAS/STING has long puzzled researchers. Riley et al () answer this question by (i) disclosing a role for Bax/Bak‐mediated MOMP beyond CytC release and (ii) revealing MIM permeabilization (MIMP) as a bridging element between apoptotic cell death and inflammation. They show that widening of Bax/Bak pores upon MOMP and CytC efflux facilitates the extrusion of the MIM into the cytosol and MIMP allows the release of matrix material, including mtDNA.…”
Section: Kinetics Of Momp‐driven Inflammationmentioning
confidence: 99%
See 1 more Smart Citation